Ecological Characteristics Of The Soil As An Indicator Of The Carrying Capacity Of Lykri Island Tourism In Eris District Of Minahasa Regency - Punuindoong, Sriwanty; Tamod, Zetly Estefanus; Rombang, Johan Alexander (Jurnal Agroekoteknologi Terapan, 2024)
This study aims to find out the ecological characteristics of the soil in particular the physical, chemical and biological properties of the soil as indicators of the carrying capacity of tourism of Likri Island. Located on Likri Island, Tendengan Dua District Eris, Minahasa Regency. Using Laboratory Survey and Analysis Methods. Soil samples are taken at 6 points, at each point taken at a soil depth of 0-30 cm and 30-60 cm. Determination of sample points is carried out by purposive sampling. It then uses matching methods for land suitability analysis as an indicator of tourism carrying capacity. Based on the results of the research, the ecological characteristics of the soil on Likri Island, namely, it has a sandy soil texture with very fast permeability and the moisture content of the airy capacity ranges at an average value of 9.33% - 11.97% and the content of nutrients N, P, K and C-organic in moderate criteria. The suitability of Likri Island land for tourism activity is moderate (S) with limiting factors of soil texture and nutrient availability. Keywords:  Soil Ecology, Tourism Carrying Capacity, Likri Island Abstrak Penelitian ini bertujuan untuk mengetahui karakteristik ekologis tanah khususnya sifat fisik, kimia dan biologi tanah sebagai indikator daya dukung pariwisata Pulau Likri. Dilaksankana di Pulau Likri Desa Tendengan Dua Kecamatan Eris Kabupaten Minahasa. Menggunakan Metode Survey dan Analisis Laboratorim. Sampel tanah diambil pada 6 titik, disetiap titik diambil pada kedalaman tanah 0-30 cm dan 30-60 cm. Penentuan titik sampel dilakukan secara purposive sampling. Kemudian menggunakan metode matching untuk analisis kesesuaian lahan sebagai indikator daya dukung pariwisata. Berdasarkan hasil penelitian karakteristik ekologi tanah di Pulau Likri, yaitu memiliki tekstur tanah berpasir dengan permeablitas sangat cepat dan kadar air kapasitas lapang berkisar pada nilai rata-rata 9,33% - 11,97% dan kandungan unsur hara N, P, K dan C-organik dalam kriteria sedang. Kesesuaian lahan Pulau Likri untuk aktivitas pariwisata adalah sedang (S) dengan faktor pembatas tekstur tanah dan ketersedian hara. Kata Kunci : Ekologi Tanah, Daya Dukung Pariwisata, Pulau Likri